Analisis Krisis Pendidikan Karakter Remaja pada Era Globalisasi di Desa Mataru Barat, Nusa Tenggara Timur - Antoneta Malaifani; Yayuk Julyyanti (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
The purpose of this study was to know the challenges of youth’s character education in the globalization era, and the factors that influenced the youth’s character education crisis in Mataru Barat Village, Mataru District, Alor Regency. The data of the study were collected through some techniques; they were observation, interviews, and documentation. The subjects of this study were teenagers, parents, and the village head. The data were analyzed through data reduction, data display and conclusions. The study showed that first, there was some negative character education on teenagers; they were unmanageable, and disobey parents, government regulations, and norms in the society. Second, the factors that influence youths’ character education were family factors: lack of attention from parents, environmental factors: lack of association with educated peers and media factors: youths spend more time on gadgets. Thus, the challenges of the globalization era were greatly influenced by the youths’ character in the West Mataru Village, which was negative social symptoms.